Thermoplastic polyurethane composites for railway applications: Experimental and numerical study of hybrid laminates with improved impact resistance. (August 2021) - Rizzo, F; Cuomo, S; Pinto, F; Pucillo, G; Meo, M
Due to the introduction of highly restrictive safety and pollution legislations in the railway industry, weight reduction has become an increasingly important topic over the last decade. Carbon fibre-reinforced polymers (CFRPs) constitute an excellent alternative to traditional materials, due to their highly specific in-plane mechanical properties. Their use in railway industry, however, is currently hindered by their weak out-of-plane properties. Bogies and underframes are often subjected to impact loadings caused by objects and debris surrounding the tracks (i.e. ice, ballast) that become airborne during the train transit and impact lower part of the carriage. While metal structures absorb impact energy via plastic deformation, barely visible impact damage can occur in CFRP, weakening the component, and often leading to catastrophic failures. This work proposes a method for the improvement of impact absorption performance of railway composite structures via the addition of a thermoplastic polyurethane (TPU) coating to CFRP laminates. The thermomechanical behaviour of the thermoplastic layer was investigated with dynamic mechanical analysis and differential scanning calorimetry analysis to optimize the manufacturing process, while damping tests were carried out to demonstrate its unaltered energy absorption ability in the final manufactured structure. TPU/CFRP plates (150 × 100 mm 2 of in-plane size) were subjected to 2, 3 and 5 J impacts, and the results were compared with those of traditional CFRP laminates. Non-destructive test (NDT; i.e. C-scan, phased array) and compression-after-impact test were carried out on the impacted samples to assess the damaged area and residual in-plane mechanical properties. Results show that the TPU layer modifies the energy absorption mechanism, preventing the propagation of damage within the CFRP and resulting in undamaged samples even at the highest energy. To predict the TPU/CFRP impact behaviour and identify the best process parameters to optimize impact energy absorption, a finite element model was developed and validated using experimental data. The comparison showed good correlation, and a fine approximation of the different impact mechanisms was observed with a maximum error of 5% between experimental and simulated output values. The experimental and numerical results show that the TPU/CFRP laminates constitute a novel solution for the manufacturing of lighter and safer railway composite structures.